Penerapan Moderasi Beragama Melalui Kurikulum Pendidikan - Aminatuz Zahroh (Bidayatuna, 2022)
One of the dynamics of Muslims today is the emergence of groups prioritising textual understanding of the Qur'an and Hadith. This group does not try to bring the knowledge of the texts to the context of their time. This group becomes radical, exclusive, intolerant, rigid, easy to disbelieve in other groups, easy to express hostility and conflict and sometimes even fight with fellow Muslims who disagree and commit acts of terrorism. On the other hand, some groups put forward contextualisation in understanding the texts excessively under the pretext of harmonising Islamic teachings with the conditions of the times. As a result, teachings emerged that were out of the text's true meaning and tended to be liberal. This group even dares to sue the qoth'i texts and interpret them based on a purely rational approach. The two groups are classified as extreme groups (tathorruf), namely, the first group is called tathorruf Yamani (extreme right), and the second group is tathorruf yasari (extreme left). The existence of these two groups is incompatible and even contradicts Islam's teachings, which are contained in the Qur'an and exemplified by the sunnah of the Prophet Muhammad. To overcome this problem, there must be a middle community (ummatan wasatha), a moderate community and mediate between the extreme right and the extreme left because the best of everything is when it is in the middle (khoirul umuuri ausathuha). Applying religious moderation through the educational curriculum is a solution to print wasatha people.